Complex network behavior in epileptic patients treated with Vagus Nerve Stimulation (VNS): VNS responders exhibit a unique pattern, different from VNS non-responders and healthy controls - Dolezalova, Irena; Chladek, Jan; Macek, Michal; Chrastina, Jan; Škvařilova, Tereza; Burilova, Petra; Erben, Stepan; Zatloukalova, Eva; Brazdil, Milan (Frontiers in Neuroscience, 2026)
IntroductionVagus nerve stimulation (VNS) represents an alternative treatment option in drug-resistant epilepsy. VNS patients can be categorized as responders (R, ≥50% seizure reduction) or non-responders (NR, < 50% seizure reduction). We demonstrate that VNS responders and VNS non-responders differ in their electrophysiological characteristics based on pre-implantation EEG analysis, specifically evaluated using relative mean power (RPW) and various information Entropy estimators computed in both he frequency and time domains. Based on the RPW and the Entropy estimators, we define and analyze the Unique Characteristics (UCs) of the individual (R and NR) groups of epileptic patients as well as Common Characteristics (CCs) that differentiate epileptic patients from healthy controls (HCs).MethodsWe investigated pre-implantation time series in 59 epileptic patients treated with VNS (24 VNS responders, 35 VNS non-responders). Subsequently, we acquired the EEG time series for 37 age- and gender-matched HCs. The EEG recordings of these three groups were filtered into standard frequency bands (theta, alpha, beta, and gamma) and segmented into eight consecutive time intervals, containing specific types of stimulation and resting states. For each of these segments, the RPW and seven Entropy estimators were calculated. We focused on the distribution of features differentiating between the epileptic patients (VNS responders or non-responders) and the HCs.ResultsWe identified 41 UCs (7 in RPW, 34 in Entropy) of VNS responders, in contrast to 19 UCs (4 in RPW, 15 in Entropy) of VNS non-responders. The UCs of VNS responders exhibit a specific pattern, showing their binding in the frequency domain to the alpha band and temporal binding to the segments of hyperventilation stimulation. The UCs of VNS non-responders were also temporally linked to hyperventilation, but mainly in the theta and gamma frequency bands.ConclusionThe VNS responders exhibit more differences when compared to HCs than VNS non-responders. These differences can be observed in RPW, but they become more pronounced when Entropy analysis is applied. It seems that the distinct response to hyperventilation is present in both VNS responders and non-responders, differentiating them from HCs. However, the binding of this response to frequency bands differs among VNS responders and non-responders. In particular, the reaction among the VNS responders is strongly associated with the alpha frequency band.